Dual-wave X-Ray absorptiometry in multiphase flow metering; RREPS-15. Radiation from Relativistic Electrons in Periodic Structures - Cherepennikov Yu. M. Yuriy Mihaylovich; Rezaev R. O. Roman Olegovich; Stuchebrov S. G. Sergey Gennadevich; Wagner A. R. Aleksandr Rudolfovich (Poster Session, 2015)
Title screen.